Facebook for dummies - Abram, Carolyn (For dummies, 2016)
Facebook is constantly changing and evolving, replacing old features and introducing new ones. This new edition of the bestselling guide quickly and easily gets you up and running on all the site has to offer. Packed with straightforward guidance that demystifies the nuts and bolts of this popular social media site, Facebook For Dummies covers everything from finding friends and planning events to uploading photos